Enhanced Photoelectrochemical Water-Splitting through Application of Layer by Layer (LBL) and Hydrothermal (HT) Methods in TiO2 and α-Fe2O3 Hierarchical Structures - Azad, Aryan; Kim, Sun Jae (Korean Journal of Metals and Materials, 2022)
Improving solar energy conversion efficiency and reducing energy loss have become critical issues in recent decades. Photoelectrochemical (PEC) water splitting provides an ideal method for solar energy harvesting and is a key factor in decreasing the use of fossil fuels. Thus, it is extremely important to identify cost-effective, highly active, and robust semiconducting photoelectrodes that can reduce the overpotential reaction and increase electrocatalytic efficiency. However, for overall water splitting, it is challenging to identify suitable photocatalysts with efficient band structures and suitable charge separation for electron-hole pairs. Water splitting is conventionally performed using independent layer-by-layer (LBL) or hydrothermal (HT) techniques. However, this research aims to produce a photoanode by applying both HT and LBL methods in sequence to reduce energy loss during the electron transfer process between the two photosystems. In this study, a TiO2 layer was deposited onto fluorine tin oxide (FTO) glass using the LBL method (TiO2/FTO). Subsequently, hematite (α-Fe2O3) thin films that were synthesized using the HT method were deposited onto TiO2/FTO glasses (Fe2O3/TiO2/FTO). The as-prepared and newly-designed photoanode Fe2O3/TiO2/FTO demonstrates a significantly high photocatalytic activity of 7.68 mA/cm2.Thus, by combining the HT and LBL methods, excellent hydrogen production performance in regard to photocatalytic water splitting was achieved. Furthermore, this hierarchical structure provides good chemical stability and is an excellent candidate for large-scale applications.